NFTs AND CREATIVITY: MONETIZATION OF DIGITAL ARTWORK VIA BLOCKCHAIN - Yanti Budiasih; Jamil Khan; Razia Khan (Journal of Social Entrepreneurship and Creative Technology, 2025)
The rise of Non-Fungible Tokens (NFTs) has revolutionized the digital art world, providing artists with new opportunities for monetization and ownership. By utilizing blockchain technology, NFTs offer an innovative solution to the challenges of digital art distribution, including issues of copyright infringement and lack of ownership. However, the broader implications for creativity and the art market remain underexplored. This research aims to explore the impact of NFTs on digital art monetization, examining how blockchain technology influences the financial success and creative autonomy of digital artists. The study seeks to understand both the opportunities and challenges presented by NFTs in the context of digital artwork. The study adopts a qualitative approach, combining literature review with case studies of successful NFT projects. Interviews with digital artists, collectors, and industry experts further complement the research, providing insights into the practical use of NFTs for artistic and financial gain. The research finds that NFTs significantly enhance the monetization potential of digital art, offering artists greater control over their work and allowing for direct transactions with buyers. Additionally, NFTs provide new models for art ownership, including royalties from secondary sales. However, challenges such as environmental concerns and market volatility are evident. NFTs represent a transformative opportunity for digital artists, fostering innovation in both creativity and monetization. While the future remains uncertain, blockchain technology is likely to continue reshaping the landscape of digital art.